Characteristics, management and outcomes of patients with severe traumatic brain injury in Victoria, Australia compared to United Kingdom and Europe: A comparison between two harmonised prospective cohort studies. Issue 9 (September 2021) - Wiegers, Eveline J.A.; Trapani, Tony; Gabbe, Belinda J.; Gantner, Dashiell; Lecky, Fiona; Maas, Andrew I.R.; Menon, David K.; Murray, Lynnette; Rosenfeld, Jeffrey V.; Vallance, Shirley; Lingsma, Hester F.; Steyerberg, Ewout W.; et al.
Highlights: Our study found that compared to UK and Europe, severe TBI patients in Victoria, Australia were younger and a higher proportion had early hypotension. In Australia, a higher proportion were discharged to a specialized rehabilitation centre, rather than another hospital or home. Compared to Europe, a higher proportion of patients in Australia and UK had intensive therapies including invasive arterial and ICP monitoring. Six months after injury, patient mortality and "favourable" independent living at 6 months were similar in all regions. Mortality was better than predicted, but fully independent living at 6 months was not. Abstract: Objective: The aim of this manuscript is to compare characteristics, management, and outcomes of patients with severe Traumatic Brain Injury (TBI) between Australia, the United Kingdom (UK) and Europe. Methods: We enrolled patients with severe TBI in Victoria, Australia (OzENTER-TBI), in the UK and Europe (CENTER-TBI) from 2015 to 2017. Main outcome measures were mortality and unfavourable outcome (Glasgow Outcome Scale Extended <5) 6 months after injury. Expected outcomes were compared according to the IMPACT-CT prognostic model, with observed to expected (O/E) ratios and 95% confidence intervals. Results: We included 107 patients from Australia, 171 from UK, and 596 from Europe. Compared to the UK and Europe, patients in Australia were younger (median 32 vs 44 vs 44 years), a larger proportion had secondary brain insults including hypotension (30% vs 17% vs 21%) and a larger proportion received ICP monitoring (75% vs 74% vs 58%). Hospital length of stay was shorter in Australia than in the UK (median: 17 vs 23 vs 16 days), and a higher proportion of patients were discharged to a rehabilitation unit in Australia than in the UK and Europe (64% vs 26% vs 28%). Mortality overall was lower than expected (27% vs 35%, O/E ratio 0.77 [95% CI: 0.64 – 0.87]. O/E ratios were comparable between regions for mortality in Australia 0.86 [95% CI: 0.49–1.23] vs UK 0.82 [0.51–1.15] vs Europe 0.76 [0.60–0.87]). Unfavourable outcome rates overall were in line with historic expectations (O/E ratio 1.32 [0.96-1.68] vs 1.13 [0.84-1.42] vs 0.96 [0.85-1.09]). Conclusions: There are major differences in case-mix between Australia, UK, and Europe; Australian patients are younger and have a higher rate of secondary brain insults. Despite some differences in management and discharge policies, mortality was less than expected overall, and did not differ between regions. Functional outcomes were similar between regions, but worse than expected, emphasizing the need to improve treatment for patients with severe TBI.